PENGARUH UKURAN PERUSAHAAN, LEVERAGE DAN PERTUMBUHAN PENJUALAN TERHADAP NILAI PERUSAHAAN DENGAN KINERJA KEUANGAN SEBAGAI VARIABEL INTERVENING PADA PERUSAHAAN MANUFAKTUR SEKTOR INDUSTRI DASAR DAN KIMIA YANG TERDAFTAR DI BEI PERIODE TAHUN 2020-2022 - Kholifah, Siti Nor; Karnadi, Karnadi; Ariyantiningsih, Febri (Fakultas Ekonomi dan Bisnis, 2024)
Primary industry and chemical sector companies are manufacturing companies that convert raw materials into semi-finished products. This study aims to determine the effect of Company Size, Leverage, and Sales Growth on Company Value with Financial Performance as an Intervening Variable. In Basic Industry and Chemical Sector Manufacturing Companies Listed on the IDX for the 2020-2022 Period. This research method uses quantitative methods. This study's data analysis and hypothesis testing used the Structural Equation Model - Partial Least Square (PLS-SEM). The results of direct influence hypothesis testing using the Smart PLS 3.0 application show that company size has a negative and significant effect on financial performance, leverage has a negative and significant effect on financial performance, sales growth has a positive and significant effect on financial performance, company size has a positive and significant effect on company value, leverage has a positive and significant effect on company value, sales growth has a negative and significant effect on company value, and financial performance has a positive and significant effect on company value. The results of the indirect effect hypothesis test show that the company size variable has a negative and significant effect on company value through financial performance, leverage has a negative and significant effect on company value through financial performance, and sales growth has a positive and significant effect on company value through financial performance.